"Kültür" ve "İdeoloji" Kavramlarına Çeviribilim Bağlamında Farklı Bir Yaklaşım - (:unkn) unknown (My University, 2004)
XX. yüzyılın ikinci yarısından itibaren çeviri alanı büyük bir gelişmeye tanık oldu. Çeviriye ilişkin geleneksel görüşlerin kapsamına yeni öğeler, yeni kavramlar girdi. "Paradigma değişikliğinin yaşanmasını sağlayan bu yeni kavramlar sayesinde çeviri yeni bir konum edindi: artık özerk bir bilim dalı olarak "çeviribilim"den söz edilebilir hale gelindi. Hiç kuşku yok ki, son yıllarda kaydedilen gelişmelerin en çarpıcısı "kültür" ve "ideoloji" kavramlarının çeviribilime verdiği destektir. Nitekim bu destekle, çevirmen çeviri metinde "görülebilir" hale gelmiştir. Böylelikle de çevirmenin varlığı azımsanmayacak ölçüde çeviri metne damgasını vurmuş ve çeviri, çevirmenin "ideolojik" seçimlerine yer veren bir eylem olarak ele alınmaya başlanmıştır.

In the second half of the XXth century, translation went through a major development: new elements, new concepts found their way into the traditional views on translation. Owing to these new concepts which led to a "paradigm shift", translation has gained a new status: that of "translation studies" as an autonomous discipline. No doubt the most striking among the developments in recent years has been the support that the concepts of "culture" and "ideology" have lent to translation studies. Through this support the translator has become "visible" within the target text. Hence, not only has the translator's presence left its mark within the target text to a degree which must not be underestimated, but also has translation come to be treated as an act that enables the translator to make his or her "ideological" choices.
A Different Approach to the Concepts of " Culture" and "Ideology" Within the Context of Translation Studies
Keywords: Dil ve Dil Bilim